Creating a culture of empowerment and accountability at St. Martin de Porres High School (B) - Howard, Liz Livingston; Waikar, Sachin; Berger, Gail ([London] : SAGE, 2016)
Change is hard for all but perhaps more difficult for school leaders and other nonprofit organizations. The role that culture plays in a mission-driven organization can often be an impediment to change. This case uses a unique education institution, St Martin de Porres School of the Cristo Rey Network, to illustrate the importance of culture in implementing change.
Originally Published in: Howard, L. L., Waiker, S., & Berger, G. (2011). Creating a Culture of Empowerment and Accountability at St. Martin de Porres High School (B). 5-410-755(B). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; St. Martin de Porres School; Organizational change -- Management -- Case studies; Educational accountability -- Case studies; Organizational behavior -- Case studies